An Investigation on University Physics Education in Bangladesh - Sikder, Md. Kabir Uddin (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2022)
The present work has revealed an inside story of university physics education in Bangladesh. The four large autonomous universities in the country were chosen to get the real reflection of physics education to perform this investigation. Sophomores, juniors, seniors, and master’s students were the participants randomly selected from these four universities at the same time of education years 2013-2014. The number of participants from each year of each university was twenty physics students, and the sample size was 320. The same questionnaire about academic resources and activities in the physics departments was used in the survey. The investigation has revealed that the theoretical results of the secondary and higher secondary students were very good but obtained without complete understanding. About 64% of students study physics against their intention as they were interested in engineering or medical courses, though the interests were not their own in every case. Many of the physics students were not attentive enough to the academic activities in the department. Many students were interested in physics research without proper awareness and induction about research. In addition, teachers were not fully engaged in the department to make the students capable of understanding and learning physics independently. As a result, only 14% of the students were consistent in their opinions and had good confidence about the promising future for physics education and research in Bangladesh. However, devoted quality teachers, students with a substantial interest in physics, and the necessary resources are required to improve physics education.